Delivering apples for cold storage to the Oregon State Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, , January 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of photograph: Installing first exhibits on grounds. Jan 08 PH Coll 727.513 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number